Solvent-resistant antistatic polyvinyl chloride composite film and preparation method thereof

CN122978615APending Publication Date: 2026-10-27GUANGDONG YUTAI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611387057.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-27

Smart Images

  • Figure CN122978615A_ABST
    Figure CN122978615A_ABST
Patent Text Reader

Abstract

The application provides a solvent-resistant antistatic polyvinyl chloride composite film and a preparation method thereof, and belongs to the field of polyvinyl chloride plastics. The polyvinyl chloride composite film comprises the following raw materials: 100 parts of polyvinyl chloride resin, 2.0-3.0 parts of aminated multi-walled carbon nanotubes, 2.5-3.5 parts of carboxylated polyaniline nanofibers, 7-10 parts of exfoliated kaolin modified by isocyanate silane coupling agent, 5-10 parts of maleic anhydride grafted polyvinyl chloride, 1.0-2.0 parts of organic tin heat stabilizer, 5-10 parts of plasticizer and 0.3-0.8 parts of polyethylene wax. The application constructs an electronic-proton dual-channel three-dimensional conductive network through aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers, and improves the interfacial compatibility by using maleic anhydride grafted polyvinyl chloride, so that the solvent resistance and antistatic performance of the polyvinyl chloride composite film are synergistically improved, and the antistatic performance is durable and stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polyvinyl chloride plastics technology, and in particular to a solvent-resistant and antistatic PVC composite film and its preparation method. Background Technology

[0002] Polyvinyl chloride (PVC) film is widely used in industrial packaging, electronic device protection, automotive interiors, medical device packaging, and advertising decoration due to its excellent mechanical properties, chemical resistance, ease of processing, and cost advantages. However, with the continuous expansion and increasing stringency of application scenarios, two inherent defects of traditional PVC film are becoming increasingly prominent: its insufficient antistatic properties and limited tolerance to organic solvents.

[0003] However, existing technologies struggle to achieve a synergistic improvement in solvent resistance and antistatic properties. When focusing on solvent resistance modification, dense cross-linked structures or filler networks hinder the dispersion of conductive fillers and the formation of conductive pathways; conversely, when focusing on antistatic modification, the addition of conductive fillers disrupts the integrity of the cross-linked network or reduces the solvent barrier effect due to increased interfacial gaps. Existing technologies primarily focus on improving individual properties through physical blending, lacking strategies for synergistic design at the molecular level. This results in weak interfacial bonding between components, making it impossible to construct a stable and robust integrated functional system. Therefore, how to synergistically improve the solvent resistance and long-lasting antistatic properties of PVC films has long been a technical challenge that has remained largely unresolved in this field. Summary of the Invention

[0004] This application provides a solvent-resistant and antistatic polyvinyl chloride composite film and its preparation method to solve the following technical problem: how to simultaneously improve the solvent resistance and antistatic properties of polyvinyl chloride composite films.

[0005] In a first aspect, embodiments of this application provide a solvent-resistant and antistatic polyvinyl chloride composite film, wherein the polyvinyl chloride composite film comprises the following raw materials in parts by weight: polyvinyl chloride resin: 100 parts, aminated multi-walled carbon nanotubes: 2.0-3.0 parts, carboxylated polyaniline nanofibers: 2.5-3.5 parts, isocyanate-based silane coupling agent modified peeled kaolin: 7-10 parts, maleic anhydride-grafted polyvinyl chloride: 5-10 parts, organotin heat stabilizer: 1.0-2.0 parts, plasticizer: 5-10 parts, and polyethylene wax: 0.3-0.8 parts.

[0006] Optionally, the preparation method of the aminated multi-walled carbon nanotubes includes the following steps: S101. Multi-walled carbon nanotubes are added to concentrated nitric acid and refluxed at 60-90°C for 2-8 hours. After post-treatment, carboxylated multi-walled carbon nanotubes are obtained. S102. The carboxylated multi-walled carbon nanotubes are dispersed in an organic solvent, thionyl chloride is added, and the reaction is carried out at 60-80°C for 2-4 hours. Then, excess thionyl chloride is removed by vacuum distillation to obtain an acyl chloride multi-walled carbon nanotube intermediate. S103. The acyl chloride multi-walled carbon nanotube intermediate is redispersed in an organic solvent, excess ethylenediamine is added, and the reaction is carried out at room temperature to 80°C for 12 to 24 hours. After post-treatment, the aminated multi-walled carbon nanotube is obtained.

[0007] Optionally, the preparation method of the carboxylated polyaniline nanofibers includes the following steps: S201. Dissolve aniline monomer and p-aminobenzoic acid in a 1 mol / L hydrochloric acid aqueous solution to obtain a reaction solution; S202. Under conditions of 0-5℃, ammonium persulfate solution is slowly added dropwise to the reaction solution. After the addition is complete, the reaction continues for 8-16 hours. After post-treatment, covalently grafted carboxylated polyaniline nanofibers are obtained.

[0008] Optionally, the molar ratio of the aniline monomer to the p-aminobenzoic acid is 1:(0.1-0.3). The molar ratio of the aniline monomer to the ammonium persulfate is 1:(1.0 to 1.2).

[0009] Optionally, the grafting rate of the maleic anhydride-grafted polyvinyl chloride is 0.8 to 1.5%.

[0010] Optionally, the organotin heat stabilizer is methyltin mercaptan or octyltin mercaptan; Optionally, the plasticizer is at least one of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, or epoxidized soybean oil.

[0011] Secondly, embodiments of this application provide a method for preparing the solvent-resistant and antistatic polyvinyl chloride composite film according to any one of the first aspects, comprising the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers are reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide as a dehydration catalyst at room temperature for 12-24 hours, and then post-treated to obtain a three-dimensional conductive network prepolymer. S2. Disperse the peeled kaolin in anhydrous toluene, add isocyanate-based silane coupling agent dropwise, stir at 80-100°C for 4-8 hours under nitrogen protection, and obtain functionalized kaolin with isocyanate groups grafted on the surface after post-treatment. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the organotin heat stabilizer, the plasticizer and the polyethylene wax are melt-mixed to obtain a mixture; S4. The mixture is formed into a film by casting to obtain the polyvinyl chloride composite film.

[0012] Optionally, the isocyanate-based silane coupling agent is 3-isocyanate-propyltrialkoxysilane.

[0013] Optionally, the melting and mixing temperature is 110–130°C, and the time is 5–10 min.

[0014] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a solvent-resistant and antistatic polyvinyl chloride composite film. Through the precise construction of intermolecular covalent bonds of each component, the solvent resistance and antistatic properties are synergistically improved. Its core logic revolves around the synergistic mechanism of conductive network stabilization and solvent penetration barrier.

[0015] Regarding the improvement of antistatic properties, this application employs a dual mechanism of prepolymerization and covalent anchoring to endow the film with durable and environmentally adaptable charge dissipation capabilities. First, aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers are pre-covalently bonded via an amidation reaction under the action of a dehydration catalyst, forming a three-dimensional conductive network prepolymer with carbon nanotubes as the electronic conductive framework and polyaniline nanofibers as the proton conductive branches. This prepolymer maintains structural integrity during subsequent processing, effectively avoiding the problems of conductive network breakage and conductive component aggregation caused by physical blending. The conjugated π-electron system of carbon nanotubes provides a high-speed electron transport channel, while the doped polyaniline nanofibers form a proton conduction channel. This dual electron and proton pathway synergistically adapts to the charge transport requirements under different humidity environments, effectively avoiding the limitation of performance degradation of a single conductive mechanism in dry or humid environments. During the melt mixing process, the isocyanate groups retained on the surface of the functionalized kaolin undergo an addition reaction with the amino groups on the surface of the three-dimensional conductive network prepolymer to form urea bonds, and / or undergo an addition-decarboxylation reaction with the carboxyl groups on the surface of the three-dimensional conductive network prepolymer to form amide bonds. This covalently anchors the entire three-dimensional conductive network prepolymer to the interior of the polyvinyl chloride matrix, preventing the conductive components from falling off, migrating, and agglomerating due to solvent swelling or external forces at the molecular interface, thus ensuring the long-term stability of the antistatic properties.

[0016] Regarding the improvement of solvent resistance, this application constructs a multi-layered solvent-resistant system through the synergistic construction of physical layered barrier and interface compatibility optimization. Peeled kaolin, with its nanoscale layered structure, is uniformly dispersed in the polyvinyl chloride (PVC) matrix, forming a dense labyrinthine barrier effect. This effectively prolongs the penetration path of solvent molecules and reduces the solvent diffusion rate, thus physically inhibiting solvent attack on the film. The main chain of maleic anhydride-grafted PVC is highly similar to the PVC matrix structure, achieving good compatibility through van der Waals forces. As a reactive compatibilizer, it promotes the uniform dispersion of peeled kaolin and the three-dimensional conductive network prepolymer in the PVC matrix, improving the interfacial bonding state and reducing stress concentration and defects caused by uneven dispersion, thereby indirectly improving the structural stability and solvent resistance of the composite film. Attached Figure Description

[0017] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 A schematic flowchart illustrating the preparation method of the solvent-resistant and antistatic polyvinyl chloride composite film provided in the embodiments of this application; Figure 2 Infrared spectra of functionalized kaolin, three-dimensional conductive network prepolymer, maleic anhydride-grafted polyvinyl chloride and composite film provided in Example 1 of this application; Figure 3 Scanning electron microscope image of the frozen brittle fracture surface of the composite film provided in Embodiment 1 of this application; Figure 4 EDS elemental surface scan of Si elemental structure of the frozen brittle fracture surface of the composite thin film provided in Embodiment 1 of this application; Figure 5 The image shows a scanning electron microscope (SEM) image of the frozen brittle fracture surface of the composite film provided in Comparative Example 5 of this application. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0021] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1 to 6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "including" and "contains" as used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist individually or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.

[0022] This application provides a solvent-resistant and antistatic polyvinyl chloride composite film, which, by weight, comprises the following raw materials: polyvinyl chloride resin: 100 parts, aminated multi-walled carbon nanotubes: 2.0-3.0 parts, carboxylated polyaniline nanofibers: 2.5-3.5 parts, isocyanate-based silane coupling agent modified peeled kaolin: 7-10 parts, maleic anhydride-grafted polyvinyl chloride: 5-10 parts, organotin heat stabilizer: 1.0-2.0 parts, plasticizer: 5-10 parts, and polyethylene wax: 0.3-0.8 parts.

[0023] In some embodiments, the preparation method of the aminated multi-walled carbon nanotubes includes the following steps: S101. Multi-walled carbon nanotubes are added to concentrated nitric acid and refluxed at 60-90°C for 2-8 hours. After post-treatment, carboxylated multi-walled carbon nanotubes are obtained. S102. The carboxylated multi-walled carbon nanotubes are dispersed in an organic solvent, thionyl chloride is added, and the reaction is carried out at 60-80°C for 2-4 hours. Then, excess thionyl chloride is removed by vacuum distillation to obtain an acyl chloride multi-walled carbon nanotube intermediate. S103. The acyl chloride multi-walled carbon nanotube intermediate is redispersed in an organic solvent, excess ethylenediamine is added, and the reaction is carried out at room temperature to 80°C for 12 to 24 hours. After post-treatment, the aminated multi-walled carbon nanotube is obtained.

[0024] In some embodiments, the preparation method of the carboxylated polyaniline nanofibers includes the following steps: S201. Dissolve aniline monomer and p-aminobenzoic acid in a 1 mol / L hydrochloric acid aqueous solution to obtain a reaction solution; S202. Under conditions of 0-5℃, ammonium persulfate solution is slowly added dropwise to the reaction solution. After the addition is complete, the reaction continues for 8-16 hours. After post-treatment, covalently grafted carboxylated polyaniline nanofibers are obtained.

[0025] In some embodiments, the molar ratio of the aniline monomer to the p-aminobenzoic acid is 1:(0.1–0.3). The molar ratio of the aniline monomer to the ammonium persulfate is 1:(1.0 to 1.2).

[0026] In some embodiments, the grafting rate of the maleic anhydride-grafted polyvinyl chloride is 0.8 to 1.5%.

[0027] In some embodiments, the organotin heat stabilizer is methyltin mercaptan or octyltin mercaptan; In some embodiments, the plasticizer is at least one of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, or epoxidized soybean oil.

[0028] It should be noted that polyvinyl chloride resin, as the matrix material, is used in an amount of 100 parts, forming the continuous phase of the composite film and providing a dispersion carrier and mechanical support for other functional components. The polar C-Cl bonds in the polyvinyl chloride molecular chain endow it with a certain polarity and cohesive energy, enabling it to form a well-compatible system with plasticizers, stabilizers, and other additives. At the same time, its semi-crystalline properties can be controlled by plasticizers during processing to achieve a transformation from rigid to flexible, adapting to the requirements of casting molding processes.

[0029] The amount of aminated multi-walled carbon nanotubes (MWCNTs) used is 2.0–3.0 parts. Their surface is modified with ethylenediamine to possess amino functional groups, which improves the dispersibility of carbon nanotubes in the organic matrix and reduces entanglement and aggregation caused by van der Waals forces. Furthermore, the surface amino groups provide active sites for subsequent covalent reactions. In the construction of the three-dimensional conductive network prepolymer, the aminated MWCNTs act as an electronically conductive framework, and their conjugated π-electron system provides a high-speed electron transport channel, endowing the composite film with charge dissipation capabilities in low-humidity environments. Simultaneously, the high aspect ratio of carbon nanotubes facilitates the formation of a percolation network in the matrix, achieving a significant improvement in antistatic properties with a relatively low dosage.

[0030] The amount of carboxylated polyaniline nanofibers used is 2.5–3.5 parts. They are prepared through the copolymerization reaction of p-aminobenzoic acid and aniline. The carboxyl groups are covalently bonded to the benzene rings of the polyaniline backbone, unlike traditional doped polyaniline, exhibiting well-defined reactive sites and structural stability. In the three-dimensional conductive network prepolymer, the carboxylated polyaniline nanofibers act as proton-conducting branches. Their NH groups can conduct charge through a proton hopping mechanism, endowing the composite film with charge dissipation capabilities in high-humidity environments. The carboxyl groups on the surface of the carboxylated polyaniline nanofibers undergo an amidation reaction with the amino groups on the surface of aminated multi-walled carbon nanotubes under the action of a dehydration catalyst, forming a covalently bonded three-dimensional conductive network prepolymer. This prepolymer maintains structural integrity during subsequent processing, avoiding network breakage caused by physical blending. Furthermore, the residual carboxyl groups and / or amino groups on the surface of the polyaniline nanofibers can undergo an addition reaction with the isocyanate groups on the surface of functionalized kaolin, anchoring the entire conductive network within the polyvinyl chloride matrix.

[0031] The amount of isocyanate-based silane coupling agent modified with exfoliated kaolin is 7-10 parts. After being exfoliated into nanoscale sheets, the exfoliated kaolin possesses a two-dimensional sheet structure with a large aspect ratio. When uniformly dispersed in polyvinyl chloride (PVC), it forms a dense labyrinthine barrier effect, effectively extending the penetration path of solvent molecules and physically inhibiting solvent diffusion. The isocyanate-based silane coupling agent achieves chemical bonding through the dehydration condensation reaction between its silane end and the hydroxyl groups on the kaolin surface. The isocyanate end is exposed on the sheet surface, providing active sites for kaolin to participate in subsequent interfacial reactions. During melt mixing, the isocyanate groups on the surface of the functionalized kaolin undergo an addition reaction with the amino groups on the surface of the three-dimensional conductive network prepolymer to form urea bonds, thereby covalently linking the kaolin to the conductive network. Simultaneously, the compatibilizing effect of maleic anhydride-grafted PVC achieves good interfacial bonding with the PVC, completely eliminating micro-interfacial gaps and preventing solvent penetration along the interface.

[0032] The amount of maleic anhydride-grafted polyvinyl chloride (PVC) is 5–10 parts. Its main chain structure is highly similar to that of the PVC matrix, and molecular-level compatibility can be achieved through van der Waals forces. As a reactive compatibilizer, it promotes the uniform dispersion of functionalized kaolin and three-dimensional conductive network prepolymer in the matrix. The cyclic anhydride in the side chain of maleic anhydride-grafted PVC is difficult to react directly with isocyanate groups. Trace amounts of moisture in the system can promote the hydrolysis and ring-opening of some cyclic anhydrides to generate carboxyl groups. The carboxyl groups generated by hydrolysis can participate in interfacial addition reactions, improve the interfacial state during the processing thermal process, enhance the interfacial bonding strength between the exfoliated kaolin and conductive network and the matrix, reduce stress concentration and defects caused by uneven dispersion, and indirectly improve the structural stability and solvent resistance of the composite film.

[0033] The amount of organotin heat stabilizer is 1.0 to 2.0 parts, and thiol methyltin or thiol octyltin is selected. Its mechanism of action is to effectively delay the thermal degradation of polyvinyl chloride during the processing by reacting the thiol group with the hydrogen chloride produced by the degradation of polyvinyl chloride and by replacing the allylic chlorine atom to inhibit the generation of conjugated polyene sequence.

[0034] The amount of plasticizer used is 5-10 parts, and at least one of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, or epoxidized soybean oil is selected. The plasticizer molecules insert into the polyvinyl chloride (PVC) molecular chains, weakening intermolecular forces and lowering the glass transition temperature, enabling PVC to achieve uniform plasticization and flow at a melting and mixing temperature of 110-130°C, meeting the requirements of the casting molding process. Simultaneously, the addition of the plasticizer improves the processing fluidity of the composite system, facilitating the uniform dispersion of functionalized kaolin and the three-dimensional conductive network prepolymer in the matrix, and reducing performance defects caused by uneven local concentrations.

[0035] The amount of polyethylene wax used is 0.3 to 0.8 parts. As a lubricant, it migrates to the metal surfaces of materials and equipment, as well as between material particles, during processing, reducing the coefficient of friction and improving melt flowability and mold release properties. Its dosage is controlled at a low level to avoid excessive lubricant accumulation in the interfacial region, which could physically block the contact between isocyanate groups and amino groups, ensuring the effective conduct of the interfacial covalent reaction.

[0036] More importantly, a clear synergistic relationship exists among the aforementioned raw materials. Aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers form a three-dimensional conductive network prepolymer through an amidation reaction, achieving complementary synergy between electronic and proton conductivity, thus meeting the antistatic requirements across a wide humidity range. Isocyanate-based silane coupling agent-modified exfoliated kaolin covalently anchors the conductive network within the matrix through the addition reaction of surface isocyanate groups with amino groups on the surface of the three-dimensional conductive network prepolymer, while simultaneously providing physical barrier properties through its layered structure. Maleic anhydride-grafted polyvinyl chloride promotes the uniform dispersion of kaolin and the conductive network within the matrix through main-chain compatibility and the action of side-chain active groups, optimizing the interfacial state. Through precise synergy between intermolecular covalent bonds and physical interactions, the components jointly achieve a simultaneous improvement in solvent resistance and antistatic properties.

[0037] Figure 1 This is a schematic flowchart illustrating the preparation method of the solvent-resistant and antistatic polyvinyl chloride composite film provided in the embodiments of this application.

[0038] Based on a general inventive concept, such as Figure 1 As shown in the embodiments of this application, a method for preparing the solvent-resistant and antistatic polyvinyl chloride composite film according to any one of the above-mentioned methods is provided, comprising the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers are reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide as a dehydration catalyst at room temperature for 12-24 hours, and then post-treated to obtain a three-dimensional conductive network prepolymer. S2. Disperse the peeled kaolin in anhydrous toluene, add isocyanate-based silane coupling agent dropwise, stir at 80-100°C for 4-8 hours under nitrogen protection, and obtain functionalized kaolin with isocyanate groups grafted on the surface after post-treatment. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the organotin heat stabilizer, the plasticizer and the polyethylene wax are melt-mixed to obtain a mixture; S4. The mixture is formed into a film by casting to obtain the polyvinyl chloride composite film.

[0039] In some embodiments, the isocyanate-based silane coupling agent is 3-isocyanate-propyltrialkoxysilane.

[0040] In some embodiments, the melting and mixing temperature is 110–130°C and the time is 5–10 min.

[0041] It should be noted that step S1 constructs a three-dimensional conductive network prepolymer via an amidation reaction. The amino groups on the surface of the aminated multi-walled carbon nanotubes and the carboxyl groups on the surface of the carboxylated polyaniline nanofibers undergo a condensation reaction catalyzed by the dehydration of N,N'-diisopropylcarbodiimide, forming a three-dimensional conductive structure covalently linked by amide bonds. This prepolymer strategy ensures a stable molecular-level bond between the electronic conductivity pathways of the carbon nanotubes and the proton conductivity pathways of the polyaniline, avoiding the problems of conductive network breakage due to shear forces or agglomeration of conductive components due to poor interfacial compatibility during physical blending. This lays a structural foundation for the stable performance of antistatic properties during subsequent processing.

[0042] Step S2 achieves surface functionalization modification of exfoliated kaolin. Through the dehydration condensation reaction between the silane end of the isocyanate-based silane coupling agent and the hydroxyl groups on the kaolin surface, isocyanate groups are chemically bonded to the kaolin sheet surface. Anhydrous toluene solvent and nitrogen protection effectively prevent hydrolysis side reactions of the isocyanate groups during the modification process, ensuring the retention of surface active sites. This functionalized kaolin acts both as a physical barrier filler, exerting a layered labyrinth effect, and as a reactive component, participating in interfacial covalent bond construction through its surface isocyanate groups during subsequent melt mixing.

[0043] Step S3 is the melt-mixing stage of the composite system. At a temperature of 110–130°C, the polyvinyl chloride (PVC) resin achieves plasticization and flow under the action of a plasticizer, the organotin heat stabilizer inhibits thermal degradation, and the polyethylene wax improves processing lubricity. All components achieve uniform dispersion under shear stress. This temperature window balances the plasticization requirements of PVC with the reactivity of isocyanate groups. The isocyanate groups on the surface of functionalized kaolin react with the amino groups on the surface of the three-dimensional conductive network prepolymer to form urea bonds, thereby covalently anchoring the conductive network within the matrix. Maleic anhydride-grafted PVC achieves compatibility with the PVC matrix through main chain structural similarity, promoting the uniform dispersion of functionalized kaolin and the conductive network prepolymer, and optimizing the interfacial bonding state.

[0044] Step S4 involves casting the molten mixture into a film using a casting method. The melt is stretched and cooled on casting rollers to solidify, forming a polyvinyl chloride composite film with uniform thickness and a stable structure. This molding process preserves the covalently anchored structure and dispersion state established during the melt mixing stage, allowing antistatic and solvent resistance properties to be synergistically expressed in the film product.

[0045] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.

[0046] Example 1 This embodiment provides a solvent-resistant and antistatic polyvinyl chloride composite film. The raw material composition of the polyvinyl chloride composite film, by weight, is as follows: 100 parts of polyvinyl chloride resin (purchased from Nantong Runfeng Petrochemical Co., Ltd., CAS No.: 9002-86-2, purity specification: 99%), 2.5 parts of aminated multi-walled carbon nanotubes, 3.0 parts of carboxylated polyaniline nanofibers, 8.5 parts of peeled kaolin modified with isocyanate-based silane coupling agent, 8 parts of maleic anhydride-grafted polyvinyl chloride (grafting rate 1.2%), 1.5 parts of thiol methyl tin heat stabilizer (purchased from Hubei Hengjingrui Chemical Co., Ltd.), 8 parts of dioctyl phthalate (CAS No.: 117-81-7), and 0.5 parts of polyethylene wax (CAS No.: 9002-88-4).

[0047] In this embodiment, the isocyanate-based silane coupling agent is 3-isocyanate-propyltrimethoxysilane (CAS No.: 15396-00-6, purchased from Nanjing Quanxi Chemical Co., Ltd., model: KH-901).

[0048] Preparation method of peeled kaolin: Kaolin (CAS No.: 1332-58-7) was prepared into a slurry with a solid content of 40%. Sodium hexametaphosphate was added as a dispersant, and then the slurry was added to a grinding mill containing quartz sand. After grinding for 60 minutes, the slurry was sieved and then subjected to sedimentation and classification to obtain flaked kaolin.

[0049] Preparation method of aminated multi-walled carbon nanotubes: S101. Take 10g of multi-walled carbon nanotubes (CAS No.: 1333-86-4, purity 95%, length 0.5~2μm, diameter 50nm) and add them to 200mL of concentrated nitric acid. Reflux at 75℃ for 5h. After the reaction is completed, cool to room temperature, centrifuge and wash with deionized water until the pH of the filtrate is 6, and vacuum dry at 80℃ for 12h to obtain carboxylated multi-walled carbon nanotubes. S102. Disperse 5g of the above carboxylated multi-walled carbon nanotubes in 100mL of N,N-dimethylformamide, add 20mL of thionyl chloride, react at 70℃ for 3h, and remove excess thionyl chloride by vacuum distillation after the reaction to obtain acyl chloride multi-walled carbon nanotube intermediate. S103. The above-mentioned acyl chloride multi-walled carbon nanotube intermediate was redispersed in 80 mL of N,N-dimethylformamide, and 30 mL of excess ethylenediamine was added. The reaction was carried out at 50 °C for 18 h. After the reaction, the intermediate was washed three times by centrifugation with anhydrous ethanol and dried under vacuum at 80 °C for 12 h to obtain the aminated multi-walled carbon nanotube.

[0050] Preparation method of carboxylated polyaniline nanofibers: S201. Aniline monomer (CAS No.: 62-53-3) and p-aminobenzoic acid (CAS No.: 150-13-0) are dissolved in 1 mol / L hydrochloric acid aqueous solution, and the molar ratio of aniline monomer to p-aminobenzoic acid is controlled at 1:0.2 to obtain the reaction solution. S202. At 2℃, ammonium persulfate solution is slowly added dropwise to the reaction solution, controlling the molar ratio of aniline monomer to ammonium persulfate to be 1:1.1. After the addition is complete, the reaction continues for 12 hours. After the reaction, the precipitate is collected by centrifugation, washed with deionized water until the filtrate is colorless, and dried under vacuum at 60℃ for 10 hours to obtain the covalently grafted carboxylated polyaniline nanofibers.

[0051] Preparation method of maleic anhydride-grafted polyvinyl chloride (MAH-g-PVC): S301. Weigh PVC resin, MAH, DCP, heat stabilizer (calcium stearate) and MgO, and mix them in a high-speed mixer at 90°C for 10 minutes to obtain a uniform premix. S302. The premixed material is added to a twin-screw extruder and subjected to melt reaction extrusion at 170°C. The residence time (i.e., reaction time) of the material in the extruder is 5 minutes. After the extrudate is cooled in a water tank and air-dried, it is pelletized using a pelletizer to obtain MAH-g-PVC products.

[0052] Based on the raw material composition of the polyvinyl chloride composite film described above, this embodiment provides a method for preparing the composite film, including the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers were reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide (10% of the total mass of the aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers) as a dehydration catalyst at room temperature for 18 h. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60 °C for 12 h to obtain a three-dimensional conductive network prepolymer. S2. Disperse the peeled kaolin in anhydrous toluene, add 3-isocyanate-propyltrimethoxysilane (8% of the mass of peeled kaolin) dropwise, stir at 90°C for 6 hours under nitrogen protection, centrifuge after reaction, wash 3 times with anhydrous toluene, and vacuum dry at 80°C for 8 hours to obtain functionalized kaolin with isocyanate groups grafted on the surface. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the thiol methyl tin heat stabilizer, the dioctyl phthalate, and the polyethylene wax are melt-mixed in an internal mixer at a temperature of 120°C for 8 minutes to obtain a mixture. S4. The mixture is formed into a film with a thickness of 0.1 mm by casting to obtain the polyvinyl chloride composite film.

[0053] Example 2 This embodiment provides a solvent-resistant and antistatic polyvinyl chloride composite film. The raw material composition of the polyvinyl chloride composite film, by weight, is as follows: 100 parts polyvinyl chloride resin, 2.2 parts aminated multi-walled carbon nanotubes, 2.7 parts carboxylated polyaniline nanofibers, 8.0 parts isocyanate-based silane coupling agent modified peeled kaolin, 6 parts maleic anhydride grafted polyvinyl chloride (grafting rate 1.0%), 1.3 parts mercaptan octyltin heat stabilizer, 7 parts diisononyl phthalate (CAS No.: 68515-48-0), and 0.4 parts polyethylene wax.

[0054] In this embodiment, the isocyanate-based silane coupling agent is 3-isocyanate-based propyltrimethoxysilane.

[0055] Preparation method of aminated multi-walled carbon nanotubes: S101. Take 10g of multi-walled carbon nanotubes and add them to 200mL of concentrated nitric acid. Reflux at 65℃ for 3h. After the reaction is complete, cool to room temperature, centrifuge and wash with deionized water until the pH of the filtrate is 6, and vacuum dry at 80℃ for 12h to obtain carboxylated multi-walled carbon nanotubes. S102. Disperse 5g of the above carboxylated multi-walled carbon nanotubes in 100mL of N,N-dimethylformamide, add 20mL of thionyl chloride, react at 65℃ for 2.5h, and remove excess thionyl chloride by vacuum distillation after the reaction to obtain acyl chloride multi-walled carbon nanotube intermediate. S103. The above-mentioned acyl chloride multi-walled carbon nanotube intermediate was redispersed in 80 mL of N,N-dimethylformamide, and 30 mL of excess ethylenediamine was added. The reaction was carried out at 40 °C for 15 h. After the reaction, the intermediate was washed three times by centrifugation with anhydrous ethanol and dried under vacuum at 80 °C for 12 h to obtain the aminated multi-walled carbon nanotube.

[0056] Preparation method of carboxylated polyaniline nanofibers: S201. Dissolve aniline monomer and p-aminobenzoic acid in 1 mol / L hydrochloric acid aqueous solution, and control the molar ratio of aniline monomer to p-aminobenzoic acid to be 1:0.15 to obtain the reaction solution; S202. At 1°C, ammonium persulfate solution is slowly added dropwise to the reaction solution, controlling the molar ratio of aniline monomer to ammonium persulfate to be 1:1.05. After the addition is complete, the reaction continues for 10 hours. After the reaction, the precipitate is collected by centrifugation, washed with deionized water until the filtrate is colorless, and dried under vacuum at 60°C for 10 hours to obtain the covalently grafted carboxylated polyaniline nanofibers.

[0057] Based on the raw material composition of the polyvinyl chloride composite film described above, this embodiment provides a method for preparing the composite film, including the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers were reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide (10% of the total mass of the aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers) as a dehydration catalyst at room temperature for 15 h. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60 °C for 12 h to obtain a three-dimensional conductive network prepolymer. S2. Disperse the peeled kaolin in anhydrous toluene, add 3-isocyanate-propyltrimethoxysilane (7% of the mass of peeled kaolin) dropwise, stir at 85°C for 5 hours under nitrogen protection, centrifuge after reaction, wash 3 times with anhydrous toluene, and vacuum dry at 80°C for 8 hours to obtain functionalized kaolin with isocyanate groups grafted on the surface. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the mercaptan octyltin heat stabilizer, the diisononyl phthalate, and the polyethylene wax are melt-mixed in an internal mixer at a temperature of 115°C for 7 minutes to obtain a mixture. S4. The mixture is formed into a film with a thickness of 0.1 mm by casting to obtain the polyvinyl chloride composite film.

[0058] Example 3 This embodiment provides a solvent-resistant and antistatic polyvinyl chloride composite film. The raw material composition of the polyvinyl chloride composite film, by weight, is as follows: 100 parts polyvinyl chloride resin, 2.8 parts aminated multi-walled carbon nanotubes, 3.3 parts carboxylated polyaniline nanofibers, 9.0 parts isocyanate-based silane coupling agent modified peeled kaolin, 10 parts maleic anhydride grafted polyvinyl chloride (grafting rate 1.4%), 1.8 parts thiol methyl tin heat stabilizer, 9 parts dioctyl terephthalate (CAS No.: 6422-86-2), and 0.7 parts polyethylene wax.

[0059] In this embodiment, the isocyanate-based silane coupling agent is 3-isocyanate-based propyltrimethoxysilane.

[0060] Preparation method of aminated multi-walled carbon nanotubes: S101. Take 10g of multi-walled carbon nanotubes and add them to 200mL of concentrated nitric acid. Reflux at 85℃ for 7h. After the reaction is complete, cool to room temperature, centrifuge and wash with deionized water until the pH of the filtrate is 6, and vacuum dry at 80℃ for 12h to obtain carboxylated multi-walled carbon nanotubes. S102. Disperse 5g of the above carboxylated multi-walled carbon nanotubes in 100mL of N,N-dimethylformamide, add 20mL of thionyl chloride, react at 75℃ for 3.5h, and remove excess thionyl chloride by vacuum distillation after the reaction to obtain acyl chloride multi-walled carbon nanotube intermediate. S103. The above-mentioned acyl chloride multi-walled carbon nanotube intermediate was redispersed in 80 mL of N,N-dimethylformamide, and 30 mL of excess ethylenediamine was added. The reaction was carried out at 65 °C for 22 h. After the reaction, the intermediate was washed three times by centrifugation with anhydrous ethanol and dried under vacuum at 80 °C for 12 h to obtain the aminated multi-walled carbon nanotube.

[0061] Preparation method of carboxylated polyaniline nanofibers: S201. Dissolve aniline monomer and p-aminobenzoic acid in 1 mol / L hydrochloric acid aqueous solution, and control the molar ratio of aniline monomer to p-aminobenzoic acid to be 1:0.25 to obtain the reaction solution; S202. At 4°C, ammonium persulfate solution is slowly added dropwise to the reaction solution, controlling the molar ratio of aniline monomer to ammonium persulfate to be 1:1.15. After the addition is complete, the reaction continues for 14 hours. After the reaction, the precipitate is collected by centrifugation, washed with deionized water until the filtrate is colorless, and dried under vacuum at 60°C for 10 hours to obtain the covalently grafted carboxylated polyaniline nanofibers.

[0062] Based on the raw material composition of the polyvinyl chloride composite film described above, this embodiment provides a method for preparing the composite film, including the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers were reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide (10% of the total mass of the aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers) as a dehydration catalyst at room temperature for 22 h. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60 °C for 12 h to obtain a three-dimensional conductive network prepolymer. S2. Disperse the peeled kaolin in anhydrous toluene, add 3-isocyanate-propyltrimethoxysilane (9% of the mass of peeled kaolin) dropwise, stir at 95°C for 7 hours under nitrogen protection, centrifuge after reaction, wash 3 times with anhydrous toluene, and vacuum dry at 80°C for 8 hours to obtain functionalized kaolin with isocyanate groups grafted on the surface. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the thiol methyl tin heat stabilizer, the dioctyl terephthalate, and the polyethylene wax are melt-mixed in an internal mixer at a temperature of 125°C for 9 minutes to obtain a mixture. S4. The mixture is formed into a film with a thickness of 0.1 mm by casting to obtain the polyvinyl chloride composite film.

[0063] Comparative Example 1 This comparative example is modified from the one disclosed in Example 1 as follows: The raw material composition of the polyvinyl chloride composite film does not contain aminated multi-walled carbon nanotubes or carboxylated polyaniline nanofibers.

[0064] Comparative Example 2 This comparative example is modified from the one disclosed in Example 1 as follows: The raw material composition of polyvinyl chloride composite films does not contain aminated multi-walled carbon nanotubes.

[0065] Comparative Example 3 This comparative example is modified from the one disclosed in Example 1 as follows: The raw material composition of polyvinyl chloride composite film does not contain carboxylated polyaniline nanofibers.

[0066] Comparative Example 4 This comparative example is modified from the one disclosed in Example 1 as follows: The raw material composition of polyvinyl chloride composite film does not contain maleic anhydride-grafted polyvinyl chloride.

[0067] Comparative Example 5 This comparative example is modified from the one disclosed in Example 1 as follows: The isocyanate-based silane coupling agent-modified peeled kaolin in the raw material composition of polyvinyl chloride composite film is replaced with unmodified peeled kaolin.

[0068] Comparative Example 6 This comparative example is modified from the one disclosed in Example 1 as follows: The raw material composition of the polyvinyl chloride composite film does not contain peeled kaolin modified with isocyanate-based silane coupling agent.

[0069] Comparative Example 7 This comparative example is modified from the one disclosed in Example 1 as follows: Aminated multi-walled carbon nanotubes were physically blended with carboxylated polyaniline nanofibers (without prepolymerization).

[0070] The performance of the polyvinyl chloride composite films obtained in Examples 1-3 and Comparative Examples 1-7 was measured, and the results are shown in Tables 1 and 2. The specific performance measurement methods are as follows: (1) Antistatic properties (surface resistivity) Using a high-resistivity meter, a specified voltage (100V) was applied to the thin film sample and kept energized for 1 minute under environmental conditions of (23±2)℃ and (50±5)% relative humidity. The surface resistance value was read and converted into surface resistivity according to the electrode size. At least 5 different locations were measured for each sample, and the arithmetic mean was taken.

[0071] (2) Solvent resistance (swelling rate and mass loss rate) Cut the film sample into squares with sides of 25mm × 25mm, dry them to constant weight in a vacuum drying oven at 60℃, weigh them, and measure their thickness. Completely immerse the sample in an organic solvent such as acetone or toluene at (23±2)℃ for 24 hours, then remove it, quickly blot the surface solvent with filter paper, and weigh it immediately. Calculate the swelling rate (the difference between the mass after immersion and the initial mass divided by the initial mass). Then, dry the sample again to constant weight, weigh it, and calculate the mass loss rate (the ratio of the mass lost after drying to the initial mass). Test at least three parallel samples in each group and take the average value.

[0072] (3) Mechanical properties (tensile strength and elongation at break) Cut the film specimen into a standard dumbbell shape and stretch it on a universal tensile testing machine at a tensile rate of 100 mm / min until the specimen breaks. Record the maximum tensile load and the change in the distance between the marks at fracture. The tensile strength is the ratio of the maximum tensile load to the initial cross-sectional area of ​​the specimen, and the elongation at fracture is the ratio of the elongation between the marks at fracture to the initial distance between the marks. At least 5 parallel specimens are tested in each group, and the arithmetic mean is taken.

[0073] Table 1. Performance of polyvinyl chloride composite films in Examples 1-3 As shown in Table 1, the surface resistivity of the polyvinyl chloride composite films in Examples 1 to 3 is 3.3 × 10⁻⁶. 8 ~7.1×10 8 The swelling rate after 24 hours of acetone immersion was 7.5%–9.8%, the mass loss rate after 24 hours of acetone immersion was 1.2%–1.7%, the tensile strength was 44.7–51.3 MPa, and the elongation at break was 244%–268%. Examples 1–3 achieved simultaneous improvement in solvent resistance, antistatic properties, and mechanical properties through the synergistic design of conductive network prepolymer construction and interfacial covalent anchoring.

[0074] Table 2 shows the properties of the polyvinyl chloride composite films in Comparative Examples 1–7. As shown in Table 2, Comparative Example 1, without the addition of aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers, completely lost the core components for constructing the conductive network, and could not form an effective charge dissipation pathway, resulting in a surface resistivity increase to 8.7 × 10⁻⁶. 12 Ω·sq (close to insulator); however, solvent-resistant components (such as functionalized kaolin, MAH-g-PVC) are still present, so the swelling rate, mass loss rate and mechanical properties are not significantly different from those in the examples.

[0075] Comparative Example 2, without the addition of aminated multi-walled carbon nanotubes, disrupted the synergistic mechanism of the electron-proton dual pathway. With the carbon nanotubes absent as the electron-conducting framework, proton conductivity relied solely on carboxylated polyaniline nanofibers. However, proton conductivity is inefficient in dry environments, leading to an increase in surface resistivity to 6.4 × 10⁻⁶. 10 The antistatic properties of the sample were significantly inferior to those of the example sample (Ω·sq); other components were unaffected, and their solvent resistance and mechanical properties were essentially the same as those of the example sample.

[0076] Comparative Example 3, without the addition of carboxylated polyaniline nanofibers, also disrupted the electron-proton dual pathway. With the polyaniline nanofibers missing as a proton-conducting branch, electronic conductivity relied solely on aminated multi-walled carbon nanotubes, leading to a decrease in the stability and efficiency of the conductive network, and an increase in surface resistivity to 2.3 × 10⁻⁶. 9Ω·sq; however, electronic conductivity still plays a part, so its antistatic properties are better than those of Comparative Example 2, and its solvent resistance and mechanical properties remain basically stable.

[0077] Comparative Example 4, without the addition of maleic anhydride-grafted polyvinyl chloride (PVC), lacked the core molecular bridge. MAH-g-PVC originally exhibited interfacial bonding through the main chain's compatibility with the PVC matrix and the side chain's active groups forming interfacial bonds with functionalized kaolin and conductive prepolymers. Without this component, the components relied solely on physical coating and dispersion, resulting in poor interfacial compatibility. Under solvent conditions, interfacial separation easily occurred, leading to a swelling rate of 17.2%, a mass loss rate of 3.9%, and a tensile strength decrease to 38.6 MPa, indicating a comprehensive deterioration in all properties.

[0078] Comparative Example 5 replaced the isocyanate-based silane coupling agent-modified peeled kaolin with unmodified peeled kaolin, thus losing the covalent interfacial bond between the kaolin and the matrix and conductive network. The unmodified kaolin was only physically dispersed in the matrix, resulting in weak interfacial bonding. Solvent easily penetrated from the interface, causing interfacial debonding, leading to a swelling rate of 16.5% and a mass loss rate of 3.5%. Simultaneously, the conductive network was also damaged due to interfacial disruption, with the surface resistivity increasing to 9.5 × 10⁻⁶. 9 Ω·sq.

[0079] Comparative Example 6, the unmodified exfoliated kaolin lacks the physical barrier filler and its interfacial anchoring effect. After the disappearance of the nanosheet maze effect in the exfoliated kaolin, the penetration path of solvent molecules in the matrix is ​​shortened, the diffusion rate is accelerated, the swelling ratio increases to 14.8%, the mass loss rate reaches 3.1%, and the solvent resistance significantly decreases. Simultaneously, the rigid support of the kaolin sheets to the matrix is ​​lost, the tensile strength decreases to 42.1 MPa, and the elongation at break decreases to 229%.

[0080] Comparative Example 7 involved the physical blending of aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers (without prepolymerization), omitting the amidation prepolymerization step. Because the conductive filler was not pre-constructed with a covalently bonded three-dimensional network structure using a prepolymer strategy, the aminated multi-walled carbon nanotubes and carboxylated polyaniline nanofibers struggled to form continuous and stable conductive pathways during subsequent melt mixing due to differences in interfacial tension and shear forces. This resulted in an incomplete conductive network structure and a surface resistivity increase to 8.3 × 10⁻⁶. 9 Ω·sq. Meanwhile, since the conductive components cannot be anchored in the matrix as a prepolymer, they are prone to migration and aggregation under the action of solvents, which weakens the interfacial stability. The swelling rate rises to 13.6% and the mass loss rate reaches 2.8%. The mechanical properties also decrease due to defects in the conductive network and insufficient interfacial bonding, with the tensile strength dropping to 43.2 MPa and the elongation at break dropping to 217%.

[0081] Figure 2Infrared spectra of functionalized kaolin, three-dimensional conductive network prepolymer, maleic anhydride-grafted polyvinyl chloride and composite film provided in Example 1 of this application.

[0082] Depend on Figure 2 It can be seen that functionalized kaolin at 2270 cm -1 A distinct asymmetric stretching absorption peak characteristic of isocyanate groups (-NCO) is visible at 1030–1100 cm⁻¹. -1 The region shows a broad absorption peak in Si-O-Si formed by silane modification; 3300–3500 cm⁻¹ -1 The area is formed by the stretching and absorption of hydroxyl groups, silanol hydroxyl groups, and OH groups that adsorb water on the surface of kaolin.

[0083] Three-dimensional conductive network prepolymer at 1640–1660 cm⁻¹ -1 A stretching vibration peak of the amide bond carbonyl group appears at 1500–1600 cm⁻¹. -1 Characteristic vibrational peaks of the polyaniline skeleton C=C / C=N are visible in the region; 3300–3500 cm⁻¹ -1 This is attributed to the NH stretching vibration absorption in the amide and polyaniline structures.

[0084] Maleic anhydride-grafted polyvinyl chloride at 1780 cm -1 1850 cm -1 The characteristic double peaks of cyclic anhydrides appear at 1710–1730 cm⁻¹. -1 The corresponding stretching vibration of the carboxyl group C=O produced by the hydrolysis of a small amount of acid anhydride is 2900 cm. -1 The vicinity exhibits saturated CH stretching vibrations in the PVC main chain; 600–700 cm. -1 The region exhibits stretching absorption of the C-Cl bond characteristic of PVC.

[0085] The final composite film was 2920 cm⁻¹ -1 The peak of the saturated CH stretching vibration was used as an internal standard for normalization comparison at 2270 cm⁻¹. -1 The near-complete disappearance of the characteristic absorption peak of -NCO at the 1640–1660 cm⁻¹ indicates that the isocyanate groups on the surface of functionalized kaolinite have participated in chemical reactions during melt processing; -1 The absorption intensity in the interval is significantly improved, approximately 1540 cm. -1 The amide II band (NH bending vibration + CN stretching vibration) appears at 3300–3500 cm⁻¹, corresponding to the newly formed urea and amide bonds in the system; -1 The NH absorption peak in the region is significantly broadened and deepened, further confirming the formation of a covalently cross-linked structure at the two-phase interface; 1030–1100 cm⁻¹ -1The characteristic absorption peaks of Si-O-Si are still retained, indicating that the kaolin sheet skeleton remains structurally intact after processing and can continue to play a solvent barrier role.

[0086] Figure 3 Scanning electron microscope image of the frozen brittle fracture surface of the composite film provided in Embodiment 1 of this application; Figure 4 This is an EDS elemental surface scan of the Si element in the frozen brittle fracture surface of the composite film provided in Embodiment 1 of this application.

[0087] Depend on Figure 3 and Figure 4 It can be seen that the functionalized kaolin is uniformly dispersed in the matrix with only a small amount of slight agglomeration; the interface between the filler and the matrix is ​​well bonded and no large number of obvious interface debonding voids were observed.

[0088] Figure 5 The image shows a scanning electron microscope (SEM) image of the frozen brittle fracture surface of the composite film provided in Comparative Example 5 of this application.

[0089] Depend on Figure 5 It can be seen that unmodified kaolin flakes are prone to forming large agglomerates, and there are obvious gaps and voids at the interface between the filler and the matrix, resulting in poor bonding between the two phases.

[0090] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A solvent-resistant and antistatic polyvinyl chloride composite film, characterized in that, The polyvinyl chloride composite film comprises the following raw materials in parts by weight: polyvinyl chloride resin: 100 parts, aminated multi-walled carbon nanotubes: 2.0-3.0 parts, carboxylated polyaniline nanofibers: 2.5-3.5 parts, isocyanate-based silane coupling agent modified peeled kaolin: 7-10 parts, maleic anhydride-grafted polyvinyl chloride: 5-10 parts, organotin heat stabilizer: 1.0-2.0 parts, plasticizer: 5-10 parts, and polyethylene wax: 0.3-0.8 parts.

2. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 1, characterized in that, The preparation method of the aminated multi-walled carbon nanotubes includes the following steps: S101. Multi-walled carbon nanotubes are added to concentrated nitric acid and refluxed at 60-90°C for 2-8 hours. After post-treatment, carboxylated multi-walled carbon nanotubes are obtained. S102. The carboxylated multi-walled carbon nanotubes are dispersed in an organic solvent, thionyl chloride is added, and the reaction is carried out at 60-80°C for 2-4 hours. Then, excess thionyl chloride is removed by vacuum distillation to obtain an acyl chloride multi-walled carbon nanotube intermediate. S103. The acyl chloride multi-walled carbon nanotube intermediate is redispersed in an organic solvent, excess ethylenediamine is added, and the reaction is carried out at room temperature to 80°C for 12 to 24 hours. After post-treatment, the aminated multi-walled carbon nanotube is obtained.

3. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 1, characterized in that, The preparation method of the carboxylated polyaniline nanofibers includes the following steps: S201. Dissolve aniline monomer and p-aminobenzoic acid in a 1 mol / L hydrochloric acid aqueous solution to obtain a reaction solution; S202. Under conditions of 0-5℃, ammonium persulfate solution is slowly added dropwise to the reaction solution. After the addition is complete, the reaction continues for 8-16 hours. After post-treatment, covalently grafted carboxylated polyaniline nanofibers are obtained.

4. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 3, characterized in that, The molar ratio of the aniline monomer to the p-aminobenzoic acid is 1:(0.1-0.3). The molar ratio of the aniline monomer to the ammonium persulfate is 1:(1.0 to 1.2).

5. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 1, characterized in that, The grafting rate of the maleic anhydride-grafted polyvinyl chloride is 0.8-1.5%.

6. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 1, characterized in that, The organotin heat stabilizer is methyl tin mercaptan or octyl tin mercaptan.

7. The solvent-resistant and antistatic polyvinyl chloride composite film according to claim 1, characterized in that, The plasticizer is at least one of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, or epoxidized soybean oil.

8. A method for preparing a solvent-resistant and antistatic polyvinyl chloride composite film according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. The aminated multi-walled carbon nanotubes and the carboxylated polyaniline nanofibers are reacted in N,N-dimethylformamide with N,N'-diisopropylcarbodiimide as a dehydration catalyst at room temperature for 12-24 hours, and a three-dimensional conductive network prepolymer is obtained after post-treatment. S2. Disperse the peeled kaolin in anhydrous toluene, add isocyanate-based silane coupling agent dropwise, stir at 80-100°C for 4-8 hours under nitrogen protection, and obtain functionalized kaolin with isocyanate groups grafted on the surface after post-treatment. S3. The polyvinyl chloride resin, the three-dimensional conductive network prepolymer, the maleic anhydride-grafted polyvinyl chloride, the functionalized kaolin, the organotin heat stabilizer, the plasticizer and the polyethylene wax are melt-mixed to obtain a mixture; S4. The mixture is formed into a film by casting to obtain the polyvinyl chloride composite film.

9. The preparation method according to claim 8, characterized in that, The isocyanate-based silane coupling agent is 3-isocyanate-based propyltrialkoxysilane.

10. The preparation method according to claim 8, characterized in that, The melting and mixing temperature is 110–130°C, and the time is 5–10 min.